Social movement discourse - Dijk, Teun A. van, 1943- author.
1 online resource
Keywords: "This is both the first systematic introduction to Discourse Studies for students and scholars of social movements and a study of discourses on the European "refugee crisis", by leading theorist, Teun A. van Dijk. Concrete examples of different kinds of discourse are vital for the study of social movements because their activities are not limited to such well-known forms of contention as marches, occupations or strikes, but also daily discursive activities, such as meetings, assemblies, interviews, press conferences, manifestos, pamphlets, banners, graffiti, websites, blogs, social media posts and everyday talk. This book proposes that empirical analyses of these discourses should go beyond the popular but vague notion of "frame" and engage in more detailed and explicit analyses of the text and talk of social movements. This is a much-needed introduction to the most important structures of discourse and a detailed theoretical account of the notion of "solidarity" defining the Refugees Welcome movement"--